Evidence of subclinical quantitative retinal layer abnormalities in AQP4-IgG seropositive NMOSD. (October 2021) - Filippatou, Angeliki G; Vasileiou, Eleni S; He, Yufan; Fitzgerald, Kathryn C; Kalaitzidis, Grigorios; Lambe, Jeffrey; Mealy, Maureen A; Levy, Michael; Liu, Yihao; Prince, Jerry L; Mowry, Ellen M; Saidha, Shiv; et al.
Background: Prior studies have suggested that subclinical retinal abnormalities may be present in aquaporin-4 immunoglobulin G (AQP4-IgG) seropositive neuromyelitis optica spectrum disorder (NMOSD), in the absence of a clinical history of optic neuritis (ON). Objective: Our aim was to compare retinal layer thicknesses at the fovea and surrounding macula between AQP4-IgG+ NMOSD eyes without a history of ON (AQP4-nonON) and healthy controls (HC). Methods: In this single-center cross-sectional study, 83 AQP4-nonON and 154 HC eyes were studied with spectral-domain optical coherence tomography (OCT). Results: Total foveal thickness did not differ between AQP4-nonON and HC eyes. AQP4-nonON eyes exhibited lower outer nuclear layer (ONL) and inner photoreceptor segment (IS) thickness at the fovea (ONL: −4.01 ± 2.03 μm, p = 0.049; IS: −0.32 ± 0.14 μm, p = 0.029) and surrounding macula (ONL: −1.98 ± 0.95 μm, p = 0.037; IS: −0.16 ± 0.07 μm, p = 0.023), compared to HC. Macular retinal nerve fiber layer (RNFL: −1.34 ± 0.51 μm, p = 0.009) and ganglion cell + inner plexiform layer (GCIPL: −2.44 ± 0.93 μm, p = 0.009) thicknesses were also lower in AQP4-nonON compared to HC eyes. Results were similar in sensitivity analyses restricted to AQP4-IgG+ patients who had never experienced ON in either eye. Conclusions: AQP4-nonON eyes exhibit evidence of subclinical retinal ganglion cell neuronal and axonal loss, as well as structural evidence of photoreceptor layer involvement. These findings support that subclinical anterior visual pathway involvement may occur in AQP4-IgG+ NMOSD.